Deteksi dan Identifikasi Cendawan Terbawa Benih Brassicaceae - Anthoni Sulthan Harahap; Titiek Siti Yuliani; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Seed quality is very critical in agricultural production, especially to gain high yield and reduce disease problems in the field. New diseases or pathogens is potentially entering a country through seed movement by import activity. This study aimed to detect and identify seed-borne fungi from Brassicaceae seeds imported from the United States and Malaysia. Seeds were incubated on 5 sheets of wet blotting paper at a temperature of 27–30 °C for 14 days following surface sterilization. Each fungus that grows on the seed was isolated on potato dextrose agar and malt extract agar for further morphological identification. The three fungi most commonly found either on the seed with or without surface-sterilization were Aspergillus flavus, Curvularia lunata and A. niger. All of the fungi were a potential pathogen in the family Brassicaceae seeds and seedlings. Important pathogen in Brassicaceae crops, i.e. Phoma lingam was also found in small amounts and only on white pak choy seeds.